2015
DOI: 10.1038/srep08197
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Pseudostellaria heterophylla with Fusarium oxysporum f.sp. heterophylla mediated by its root exudates in a consecutive monoculture system

Abstract: In this study, quantitative real-time PCR (qPCR) was used to determine the amount of Fusarium oxysporum, an important replant disease pathogen in Pseudostellaria heterophylla rhizospheric soil. Moreover, HPLC was used to identify phenolic acids in root exudates then it was further to explore the effects of the phenolic acid allelochemicals on the growth of F. oxysporum f.sp. heterophylla. The amount of F. oxysporum increased significantly in P. heterophylla rhizosphere soil under a consecutive replant system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 26 publications
(27 reference statements)
1
49
0
Order By: Relevance
“…36 Furthermore, FA that was secreted by Pseudostellaria heterophylla roots also stimulated sporulation of the pathogen Fusarium oxysporum f. sp heterophylla and induced plant wilt disease. 12 Previously, our study showed that watermelon wilt disease can be alleviated by rice/watermelon intercropping management. 21 FON is suppressed in vitro by root exudates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Furthermore, FA that was secreted by Pseudostellaria heterophylla roots also stimulated sporulation of the pathogen Fusarium oxysporum f. sp heterophylla and induced plant wilt disease. 12 Previously, our study showed that watermelon wilt disease can be alleviated by rice/watermelon intercropping management. 21 FON is suppressed in vitro by root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The accumulation of plant root exudates in the rhizosphere after monoculture causes rapid pathogen proliferation in replanted soil, which negatively impacts soil quality, crop health, and yield. 12,20 Watermelon wilt disease was found to be alleviated by intercropping with aerobic rice. 21 This alleviation was due to suppression of FON pathogen spore germination and sporulation by rice root exudates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies by culture-dependent and culture-independent analysis demonstrated that F. oxysporum and other Fusarium spp. are the main causative agents of wilt and rot disease of this plant (Zhao Y. et al, 2015; Wu L. et al, 2016). Our previous studies have demonstrated that the phenolic acids identified in the root exudates of P. heterophylla could significantly inhibit the growth of beneficial Burkholderia sp.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Pseudomonas catalysed (-)-catechin conversion into 3,4-dihydroxybenzoic acid, and 3,4-dihydroxybenzoic acid showed a higher phytotoxicity than (-)-catechin (Masuda et al 2007); Bacillus aquimaris involved in the degradation of allelopathic m-tyrosine (Khan et al 2013); F. oxysporum, a replant disease pathogen in P. heterophylla rhizospheric soil, increased sharply under a consecutive-replant system, and some phenolic acids promoted the growth of F. oxysporum f.sp. (Zhao et al 2015). In production of R. glutinosa, 15 to 20 years of crop rotation is taken for its replanting (Yang et al 2011b).…”
Section: Discussionmentioning
confidence: 99%